THE EXPERIMENT OF THE COMPLEX INSPECTION OF THE RAILROAD BRIDGE PIER - Usachenko, B. M.; Sergienko, V. M.; Kurochka, A. A. (Science and Transport Progress, 2010)
The procedure and results of a visual inspection and vibrosonic diagnostics of the railroad bridge pier are described. The spatial model of the pier with an arrangement of large cracks is presented.